2020
DOI: 10.1155/2020/8889333
|View full text |Cite
|
Sign up to set email alerts
|

A New Erosive Burning Model of Solid Propellant Based on Heat Transfer Equilibrium at Propellant Surface

Abstract: Erosive burning refers to the augmentation of propellant burning rate appears when the velocity of combustion gas flowing parallel to the propellant surface is relatively high. Erosive burning can influence the total burning rate of propellant and performance of solid rocket motors dramatically. There have been many different models to evaluate erosive burning rate for now. Yet, due to the complication processes involving in propellant and solid rocket motor combustion, unknown constants often exist in these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this paper, two different erosive burning models are used for comparison purposes. The first is the Ma model [17]. In this model, the total burning rate comprises the following two components: the normal burning rate and the erosive burning rate.…”
Section: Erosive Burningmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, two different erosive burning models are used for comparison purposes. The first is the Ma model [17]. In this model, the total burning rate comprises the following two components: the normal burning rate and the erosive burning rate.…”
Section: Erosive Burningmentioning
confidence: 99%
“…The code used in this paper evolved from the code developed by the authors in Ref. [17], to accommodate the star grain in the SRM studied in this paper. During the computation, the SRM For the star grain with an arc at the star tip, the burning process of the grain can be divided into four stages.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the most recent investigations on the erosive burning phenomenon have demonstrated that the experimental calibration of the models is still necessary [12], the erosive burning rate is proportional to the heat flux on the propellant surface [13], and the quasi-one-dimensional simulations of the internal ballistics of the solid rocket motors using the two-dimensional grains have acceptable accuracy for performance prediction [14]. It should be emphasized that erosive burning is not always harmful, but can sometimes be used to improve the performance especially for the solid rocket motors with progressive burning propellant grains [15].…”
Section: Introductionmentioning
confidence: 99%